The military turn in Turkey's political economy: Defense industry, growth strategy, and power bloc formation - Akca, Ismet; Ozden, Baris Alp (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
While there is no shortage of scholarship on Turkey's military industry, the field lacks theoretically grounded and critical political-economy analyses to explain the implications of this recent 'military turn.' This study aims to fill this gap by situating the development of the military-industrial complex within Turkey's shifting growth strategies and the coalition of key actors that underpin them. The military industry plays a crucial role through two main mechanisms. First, it establishes a network of relationships that fosters the development of a relatively high value-added sector, creating a secure environment for capital accumulation across diverse capital groups. Second, it supports a foreign policy and trade strategy that increasingly relies on military power.
Keywords: Military-industrial complex; Growth strategies; Power blocs; Foreign policy; FOREIGN-POLICY; COUNTRIES; Government & Law